Plasticity based interface model for failure modelling of unreinforced masonry under cyclic loading - Kumar, P. V. S. K.; Rajagopal, Amirtham; Pandey, Manoj (Vietnam Journal of Mechanics, 2020)
In this work our objective is to understand the failure behaviour of unreinforced masonry under in-plane cyclic loading. For this purpose we proposed a plasticity based interface model consists of a single yield surface criteria which is a direct extension of Mohr-Coulomb criteria with a tension cut and compression cap and a back stress vector is introduced as a mixed hardening law variable in the adopted yield surface to capture the unloading/reloading behaviour of masonry under cyclic loading. A simplified micromechanical interface modelling approach is adopted to capture all the failure modes of masonry. The integration of the differential constitutive equation is done by using implicit Euler backward integration approach and the obtained non-linear set of equations are solved by a combined local/global Newton solver. The proposed constitutive model is implemented in ABAQUS by writing UMAT (user-defined subroutine) and the obtained numerical results are compared with experimental results available in the literature.